Human Leukocyte Antigen Class II Haplotypes Affect Clinical Characteristics and Progression of Type 1 Autoimmune Hepatitis in Japan - Umemura, Takeji (Public Library of Science, 2014)
Although we earlier demonstrated that the human leukocyte antigen (HLA) DRB1*04:05 allele was associated with susceptibility to autoimmune hepatitis (AIH) in Japan, the precise relationship of HLA haplotype and the role of amino acid alignment with disease susceptibility and progression has not been fully clarified. We reinvestigated HLA class I A, B, and C and HLA class II DRB1, DQB1, and DPB1 alleles and haplotypes in a larger new cohort of 156 Japanese patients with type 1 AIH and compared them with the published data of 210 healthy subjects. The DRB1*04:05-DQB1*04:01 haplotype was significantly associated with AIH susceptibility (30% vs. 11%, P = 1.2×10(−10); odds ratio [OR]  = 3.51) and correlated with elevated serum IgG (3042 vs. 2606 mg/dL, P = 0.041) and anti-smooth muscle antigen positivity (77% vs. 34%, P = 0.000006). No associations with HLA-DPB1 alleles were found. The HLA A*24:02 and C*01:02 alleles were associated with disease susceptibility (corrected P = 0.0053 and 0.036, respectively), but this likely constituents of a long ranged haplotype including DRB1*04:05-DQB1*04:01 haplotype. Conversely, the DRB1*15:01-DQB1*06:02 haplotype was associated with protection from both disease onset (5% vs. 13%, P = 0.00057; OR = 0.38) and the development of hepatocellular carcinoma (25% vs. 5%, P = 0.017; OR = 6.81). The frequency of the DRB1*08:03-DQB1*06:01 haplotype was significantly higher in patients who developed hepatic failure (22% vs. 6%, P = 0.034; OR = 4.38). In conclusion, this study established the role of HLA haplotypes in determining AIH susceptibility and progression in the Japanese population. Additional sequencing of the entire HLA region is required to more precisely identify the genetic components of AIH.